A DNA Aptamer Targeting Galectin-1 as a Novel Immunotherapeutic Strategy for Lung Cancer - Yao-Tsung Tsai; Chen-Hsien Liang; Jin-Hsuan Yu; Kuan-Chih Huang; Chia-Hao Tung; Jia-En Wu; Yi-Ying Wu; Chih-Hsien Chang; Tse-Ming Hong; Yuh-Ling Chen (Elsevier, 2019)
Galectin-1 (Gal-1) is a pleiotropic homodimeric β-galactoside-binding protein with a single carbohydrate recognition domain. It has been implicated in several biological processes that are important during tumor progression. Several lines of evidence have indicated that Gal-1 is involved in cancer immune escape and induces T cell apoptosis. These observations all emphasized Gal-1 as a novel target for cancer immunotherapy. Here, we developed a novel Gal-1-targeting DNA aptamer (AP-74 M-545) and demonstrated its antitumor effect by restoring immune function. AP-74 M-545 binds to Gal-1 with high affinity. AP-74 M-545 targets tumors in murine tumor models but suppresses tumor growth only in immunocompetent C57BL/6 mice, not in immunocompromised non-obese diabetic (NOD)/severe combined immunodeficiency (SCID) mice. Immunohistochemistry revealed increased CD4+ and CD8+ T cells in AP-74 M-545-treated tumor tissues. AP-74 M-545 suppresses T cell apoptosis by blocking the binding of Gal-1 to CD45, the main receptor and apoptosis mediator of Gal-1 on T cells. Collectively, our data suggest that the Gal-1 aptamer suppresses tumor growth by blocking the interaction between Gal-1 and CD45 to rescue T cells from apoptosis and restores T cell-mediated immunity. These results indicate that AP-74 M-545 may be a potential strategy for cancer immunotherapy. Keywords: immunotherapy, galectin-1, aptamer, lung cancer